The Impact of Instrumental Music Therapy on Student’s Anxiety Facing College Entrance Examination: Pengaruh Terapi Musik Instrumental Terhadap Kecemasan Siswa dalam Menghadapi Ujian Masuk Perguruan Tinggi Negeri - Firdiana Invira Rahma; Sutejo; Sarka Ade Susana (Caring : Jurnal Keperawatan, 2023)
SBMPTN is a joint selection to enter state universities. Intense competition between participants can trigger student anxiety. Excessive anxiety can affect the escape of the participants. The treatment given was in the form of instrumental music therapy. Music is therapeutic, which means it can heal. Instrumental music therapy can provide a sense of relaxation and comfort for listeners. It is known that the effect of giving instrumental music therapy on student’s anxiety in facing state university entrance exams. The research subjects were 110 students consisting of science and social studies majors. The research instrument used the Depression Anxiety Stress Scale 42 (DASS-42). Hypothesis testing was analyzed using Wilcoxon and Mann Whitney. There are differences in anxiety between pretest and posttest on instrumental music therapy (p value = 0.000) and leaflets (p value = 0.000). There was a significant difference in the treatment of instrumental music therapy as evidenced by the difference in the mean anxiety between the intervention group and the control group, which obtained a Sig (p value) of 0.000 (p value <0.05). Providing instrumental music therapy can have a significant effect on reducing student anxiety in facing state university entrance exams.   SBMPTN merupakan seleksi bersama masuk perguruan tinggi negeri. Persaingan ketat antar peserta dapat memicu kecemasan siswa. Kecemasan berlebih dapat memengaruhi kelolosan para pesertanya. Perlakuan yang diberikan berupa terapi musik instrumental. Musik bersifat terapeutik yang artinya bisa menyembuhkan. Terapi musik instrumental dapat memberikan rasa rileks dan nyaman bagi pendengarnya. Penelitian ini berjenis quasi experimental design dengan rancangan pretest and posttest control group design. Subjek penelitian sebanyak 110 siswa terdiri dari jurusan IPA dan IPS. Instrumen penelitian penggunakan Depression Anxiety Stress Scale 42 (DASS-42). Uji hipotesis dianalisis menggunakan Wilcoxon dan Mann Whitney. Terdapat perbedaan kecemasan antara pretest dan posttest pada terapi musik instrumental (p value = 0.000) dan leaflet (p value  = 0.000). Terdapat perbedaan yang signifikan dari perlakuan terapi musik instrumental dibuktikan dengan selisih mean kecemasan antara kelompok intervensi dan kelompok kontrol didapatkan Sig (p value) yakni 0.000 (p value<0.05). Pemberian terapi musik instrumental dapat memberikan pengaruh yang signifikan terhadap penurunan kecemasan siswa dalam menghadapi ujian masuk perguruan tinggi negeri.